Factor of work accident in Indonesian construction site: Medan, Indonesia - Teuku Muhammad Johan, Teuku Muhammad Zulfadly (2017)
Indonesia experienced poor occupational safety and health issue because the work accident‟s rate still increased. In fact, 32% of the accidents are derived from construction industry. Medan as one of big city in Indonesia was chosen to run this research following some fatal accidents happened in its construction site. 6 categories of work accident's factors have been taken account for this research which consists of unsafe equipment, unsafe work site, unique nature of industry, unsafe method, human error and poor management. The objective of this research is to identify the factor that significantly contributes to work accident in Medan construction site as well as the preventive solution. The objective is assessed based on 2 respondent‟s perspectives which consist of Indonesian construction board and contractors in Medan. The perception of Indonesian construction board‟s Expert has been studied to identify the factor of work accident and preventive solution on all of the factors. Contractor‟s perception which represented by professional worker also has been investigated to identify the accident‟s factors which happened mostly in Medan construction site. 2 methods of data collection are applied namely interview and questionnaire. Interview is used to obtain the data from construction board‟s expert while questionnaire is used to collect the data from contractors. Interview data has been analyzed using content analysis while the questionnaire data was analyzed using descriptive and explanatory analysis. In conclusion, Expert of Indonesian construction board perceived human error as most impactful factor while contractor perceived unique nature of industry as highest factor contribute of work accident in Medan. The preventive solutions are basically recommended in term of providing better monitoring program, improve supervision and training to workers, select competent worker and periodically check all of the equipment.